Compensação da forma de onda de um inversor PWM utilizando uma técnica de controle repetitivo - Vinícius Cordeiro Durães Araujo (2011)
Inverters for UPS systems must provide a regulated output voltage and low value of total harmonic distortion - THD. This paper presents a study of several control techniques for the output stage of a UPS system. We performed a literature review of control strategies that address this goal. The use of a digital control technique to regulate the RMS value of the waveform associated with repetitive integral action is evaluated for low cost PWM inverters. As a result of repetitive integral action, this strategy of digital control reduces the steady-state error and distortions caused by periodic disturbances such as nonlinear loads. In addition, the digital control technique measures only the output voltage, reducing the cost with sensors.